Empowering Communities with Integrated Pest Management for Sustainable Agriculture - Aulia, Muhammad Reza; Eryanto , Oktoni; Siregar , Mawaddah Putri Arisma; Yuhendra , Alfis; Aminah , Siti (Universitas Ahmad Dahlan, 2024)
Background: The aim of this community development initiative, centered around community engagement, is to address the pressing issue of declining agricultural productivity due to pest infestations in the Asahan Regency, a developing area. Through educational and training programs, the initiative seeks to advocate for Integrated Pest Management (IPM) practices and safe pesticide usage among farmers, while also addressing the environmental impacts of chemical pesticide use. Contribution: The primary focus is to gauge the impact of these initiatives in fostering sustainable and environmentally responsible agricultural practices in Asahan Regency, ultimately enhancing the overall well-being of the farming community. Method: A total of 50 farmers actively participated in these programs, all of whom derived substantial benefits that directly contributed to the improvement of their livelihoods. Results: The implementation of IPM with a community development approach has the potential to significantly enhance paddy rice productivity while promoting sustainable agriculture Conclusion: By involving the local community, improving pest control methods, reducing environmental impact, and fostering knowledge sharing, this approach can lead to positive outcomes for both farmers and the environment